The impact of entrepreneurial orientation and company innovation on the business performance of manufacturing SMEs - Taan, Hapsawati; Alam, Heldy Vanni; Rukayah, Sitti; Ismail, Yulinda Lubis; Arsyad, Nur Fadilah (International Journal of Management and Sustainability, 2023)
This study examines the importance of entrepreneurial orientation in relation to innovation and performance within the context of manufacturing small and medium-sized enterprises (SMEs). Additionally, it looks into the impact of innovation on manufacturing SMEs' performance as well as the impact of entrepreneurial innovation on those SMEs' performance. The research population involved all manufacturing SMEs in Gorontalo Province, Indonesia. Sampling processes apply the nonprobability sampling method. The selection of cluster sampling, involving 150 samples, was carried out purposively. Data analysis was carried out using structural equation modeling with software called Analysis of Moment Structures (Amos). The findings indicate a favorable and statistically significant relationship between entrepreneurial orientation and both innovation and performance in manufacturing small and medium-sized enterprises (SMEs). Furthermore, the integration of entrepreneurial orientation and innovation inside small and medium-sized firms (SMEs) operating in the manufacturing sector has been identified as having a substantial and advantageous influence on their overall performance. It is noteworthy that the introduction of innovation within a firm does not have any discernible influence on the operational performance of small and medium-sized enterprises (SMEs) in the manufacturing sector. This study suggests that people involved in manufacturing SMEs must boost their performance by being proactive towards an entrepreneurial orientation. It is recommended for SMEs in Gorontalo City to enhance the implementation of entrepreneurial orientation for the development of their businesses. It is also essential to consider the factors of proactive attitudes, enthusiasm, and risk-taking attitudes.